(untitled) (Bioagro, 2023)
Medicinal plants are an inexhaustible source of molecules with several biological activities. The main objective of this research was the evaluation of the antimitotic and genotoxic effect by the Allium cepa test of the methanolic extract of the leaves of Peganum harmala, a spontaneous plant from the arid zones of Algeria (Timzerth, Laghouat). Different concentrations (1, 4, 10, and 16 mg∙mL-1) of the extract, as well as two standards (colchicine and quercetin) at 1 mg∙mL-1 concentration were tested. Mitotic index (MI), limit value for cytotoxicity (LVC), phase index (PI), and aberration indexes (AI) were calculated, and different aberrations were identified in treated meristematic onion cells. Statistical analyses by ANOVA and Newman-Keuls test were performed. The results confirmed our previous findings that the methanolic extract has an anti-mitotic effect similar to that of the standards. The increase in extract concentrations was accompanied by a decrease in the various indexes calculated. The extracts blocked mitosis in prophase which was predominantly present, and caused increase in abnormalities, represented by dominant rates of agglutinations, chromosomal fragmentations and binuclear cells. confirmed that the effect was independent of concentrations, though to varying degrees.